Ministry Of Finance Decree No. 614 Of The Year 2020 Amending Certain Provisions Of The Executive Regulations Of The Law Organizing The Contracts Concluded By Public Entities As Issued By Minister Of Finance’s Decree No. 692 Of The Year 2019 = وزارة المالية قرار رقم 614 لسنة 2020 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم التعاقدات التى تبرمها الجهات العامة الصادرة بقرار وزير المالية رقم 692 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic